Handling Criminal Cases of Corruption Involving Active Indonesian National Army (TNI) Soldiers - Gusman, Delfina (Journal of Law, Politic and Humanities, 2023)
Based on the set of laws related to eradicating corruption and the class of laws within the military scope in Indonesia, whether the involvement of active TNI soldiers in criminal acts of corruption in enforcement is processed through the Military Court or the Corruption Crime Court as the court in General Justice environment? And what about the authority of the Corruption Eradication Commission (KPK) in this matter?.